Methodological Principles of the Accounting for Intangible Assets from the View of National and International Standards - Dmitrenko, I. M.; Kostyrko, R. O.; Bondar, V. P. (Statistics of Ukraine, 2018)
The article defines the basic accounting items that determine the impact on the complex of methodological principles of accounting and reporting generalization of information about intangible assets. The complex of basic accounting positions for intangible assets is proposed in the following composition: definition of the object of accounting; method of identification; response to goodwill; how to receive and how to pay; the criteria for recognizing the asset is intrinsic; method of initial assessment; revaluation model; response to impairment; conditions for the choice and application of methods of accrual of depreciation; directions of disclosure. The key methodological principles of accounting for intangible assets are systematized on the basis of a comparative analysis of the provisions of national and international standards. As a result of the comparative analysis, both conceptually similar principles and those that are characterized by significant differences are established. In particular, this applies to: the ways of obtaining and payment of the intangible assets, for which the IAS does not provide for the free receipt and payment of an intangible asset to the authorized capital of the enterprise, which emphasizes the nature of such assets in view of the obligation to receive future economic benefits; the definition of the value of internally generated goodwill is precisely in IAS, which contributes to a reasonable separation from the value of its own intangible assets in the event of the merger of enterprises; the initial valuation of the intangible assets, for which IAS prioritizes the valuation at cost rather than fair value, as defined by National Accounting Standards, due to the dependence of the usually unpopular phenomenon - the existence of an active market for such assets; the variability of the choice of depreciation methods for the intangible assets, for which IAS offers more opportunities to take into account the specifics of the use of these objects during the formation of depreciation costs; directions of disclosure of the intangible assets information in the notes to the financial statements, which are clearly defined in the IAS. Comments on the conditions for the implementation of the requirements of national and international standards for the accounting of intangible assets at the level of economic entities from the point of view of the established differences and their consequences are given. It is proved that a much higher level of transparency of information about intangible assets is provided in the case of accounting and financial reporting by entities in accordance with the requirements of IAS and IFRS.